Analysis of Some Punishment Practices Based on Legal-Historical Principles of Iranian Society: Qajar Dynasty Case Study - Rezaeian Koochi, Mohammad Reza; Shavaki, Ghadir Najafzadeh; Moradi, Sajad (Journal of History Culture and Art Research, 2017)
As one of their main functions to maintain political power, ruling dynasties in Iran always tried to establish social security and confront any events that might disrupt stability in the country. Therefore, various penalties had been meted out for perpetrators of such phenomena including social unrest, robbery, acting in disobedience to the orders of the Shah and other officials, disruption to economic activities and financial affairs of the people, murder, rape, drunken brawls in public places, and the like. These punishments were performed in various manners by non-religious jurisdictions or at the behest of the Shah, local rulers, or other security officials without any established procedures. Most of the punishments were based on the expediency of the government rather than the expediency of religion or jurisprudence. Rulers determined the manner of punishment on the basis of popular preferences. This type of conventional punishment, as opposed to legal or religious punishment, was quite common during the Qajar era, as a tool for countering the widespread social unrest. This has been reflected in the chronicles of many historians and in the diaries written by many European tourists visiting Iran during the period. The present study deals with various types of punishment of criminals and the manner of practicing such punishments during the Qajar era before the Constitutional Revolution. Findings of the study show that the punishments in the period were not based on any legal standards and that decisions of the Shah and other government officials determined the manner of performing punishments, often with much violence and harshness.